Narrative Writing and Linguistic Intelligence: An Empirical Study in Indonesian Junior High Classrooms - Asih Riyanti; Maman Suryaman (AL-ISHLAH: Jurnal Pendidikan, 2025)
Every student possesses innate intelligences that influence their learning potential. Linguistic intelligence, in particular, plays a key role in developing narrative writing skills. This study investigates the effectiveness of linguistic intelligence in enhancing narrative writing among seventh-grade students and explores the challenges faced by both students and teachers during the learning process. This experimental study was conducted at State Middle School 13 Tarakan, North Kalimantan, Indonesia. The subjects consisted of two seventh-grade classes (Class A and Class B), each comprising 34 students. Data were collected through questionnaires and narrative writing tests. The experimental group received instruction based on the VAK (Visual, Auditory, Kinesthetic) learning model tailored to linguistic intelligence, while the control group followed standard instruction. Data were analyzed using mean scores and standard deviations, with hypothesis testing to determine significance. The experimental group showed significant improvement in narrative writing skills. The average final test score in the control group was 74.14, while the experimental group achieved 82.87, compared to their pre-test average of 69.82. Hypothesis testing indicated that linguistic intelligence significantly influenced students' writing abilities (Ho rejected). Findings suggest that integrating linguistic intelligence through VAK learning strategies enhances students' ability to express ideas in narrative form. However, both students and teachers faced challenges such as limited motivation, lack of imagination, and difficulties understanding narrative structure.